A novel approach for simulating a sawing process with reduced simulation time. (June 2023) - Möhring, Hans-Christian; Menze, Christian; Drewle, Konstantin; Fackelmann, Dennis; Stegmann, Jan; Kabelac, Stephan
Abstract: The numerical simulation of machining processes enables the analysis of thermo-mechanical effects and can be used to predict process-specific quantities such as cutting force and chip shape. This involves, however, a great amount of computational effort and time depending on the model design. Basically, a simulation can be carried out two- or three-dimensionally. Due to the lower computational effort, 2D simulations were often used in the past to analyse the machining properties. In orthogonal cutting, this leads to a good approximation to the real processes if a suitable ratio between cutting width and depth of cut is applied. Nevertheless, most industrially relevant machining processes cannot be completely simulated with a 2D simulation. For these purposes, 3D simulations must be created. This requires a much greater computational effort, which increases the simulation time. This paper shows an approach to determine the cutting force and the information about the chip shape during sawing (bound orthogonal cutting) with a shortened calculation time. This was achieved by dividing the entire cut into 2D and 3D areas. The ratio between the cutting width and the depth of cut defines the criterion for the division. When it was greater than 10, the cutting process between the corner radii was assumed to be a plane two-dimensional strain state. The results showed a good agreement of the cutting force calculated from the 2D–3D simulation approach with experimental investigations and a 3D simulation. The computing time could be reduced by more than 50%.